Answer:
Explanation:
Since both a point on this new line and the slope of the line are given, we use the "point-slope equation of a straight line," that is, y - k = m(x - h).
Here we are told that the point is (2, -1/2), so h = 2 and k = -1/2.
The slope, m, is 3. Thus,
y - k = m(x - k) becomes y + 1/2 = 3(x - 2)
Check: does the point (2, -1/2) satisfy this equation?
Is -1/2 + 1/2 = 3(2 - 2)? Yes. So this equation must be correct. Please ensure that you have copied down all of the possible answers correctly.